2010
DOI: 10.1080/09583150903438439
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of arbuscular mycorrhiza and other biocontrol agents in managingFusarium oxysporumf. sp.Cubenseinfection in banana cv. Neypoovan

Abstract: Panama wilt of banana caused by Fusarium oxysporum f. sp. cubense (race 1) is a serious disease devastating the important cultivar Neypoovan (syn Elakki Bale AB) in southern India. Chemical control methods are not very effective in controlling the disease. The objective of this study was to evaluate biocontrol agents (BCAs) under controlled and field conditions for their efficacy against the pathogen and to detect and quantify the reduction in FOC population. Arbuscular mycorrhizal (AM) fungi, Trichoderma harz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Maçã, especially under low concentration of Foc inoculum (Borges et al, 2007). Also, the pathogen population in roots of banana plants at 7 months after treatment with a combination of G. mosseae and T. harzianum was significantly reduced, as measured by ELISA (Mohandas et al, 2010). In the field, banana plants pre-treated in the nursery with G. clarum had higher biomass than untreated plants, and showed lower FWB incidence (67%), compared to the untreated control (88%).…”
Section: Biological Control Agents and Their Modes Of Action: Actualmentioning
confidence: 99%
“…Maçã, especially under low concentration of Foc inoculum (Borges et al, 2007). Also, the pathogen population in roots of banana plants at 7 months after treatment with a combination of G. mosseae and T. harzianum was significantly reduced, as measured by ELISA (Mohandas et al, 2010). In the field, banana plants pre-treated in the nursery with G. clarum had higher biomass than untreated plants, and showed lower FWB incidence (67%), compared to the untreated control (88%).…”
Section: Biological Control Agents and Their Modes Of Action: Actualmentioning
confidence: 99%
“…In the decade since biocontrol work on Fusarium wilt of banana was last reviewed (Ploetz, 2004), the above trends have continued, as few field studies have been reported and most publications describe only lab and greenhouse research (Borges et al, 2007;Fishal et al, 2010;Forsyth et al, 2006;Lian et al, 2008;Mohandas et al, 2010;Nel et al, 2006a,b;Sun et al, 2011;Thangavelu and Jayanthi, 2009;Thangavelu and Mustaffa, 2012;Ting et al, 2010;Wang et al, 2013;Weber et al, 2007;Wu et al, 2013;Zacky and Ting, 2013). In two exceptional situations, field results were reported: the best treatment of Thangavelu and Jayanthi (2009) resulted in a nonsustainable incidence of 20% after 8 months, and in another study, promising greenhouse treatments failed in the field; in it, Belgrove et al (2011) noted that "… neither the nonpathogenic F. oxysporum, P. fluorescens, nor combinations thereof reduced Fusarium wilt development significantly."…”
Section: Biocontrolmentioning
confidence: 93%
“…Height and stem diameter increment/loss were computed as the difference between the final and initial data taken during the experiment. The effectiveness of the artificially induced suppressive soil was assessed based on disease incidence (%) and disease progression, estimated by using the area under the disease progress curve (AUDPC) which was compared statistically among treatments [15] every week on a six-week period. Sample plants were sectioned longitudinally to confirm the presence of vascular lesions characteristic of FocR4 infection.…”
Section: Methodsmentioning
confidence: 99%